Search for Higgs Boson Pair Production in the γγbb¯ Final State using pp Collision Data at s√=8TeV from the ATLAS Detector - Onofre, A. (2015)
Searches are performed for resonant and non-resonant Higgs boson pair production in the hh→γγbb¯ final state using 20 fb−1 of proton--proton collisions at a center-of-mass energy of 8TeV recorded with the ATLAS detector at the CERN Large Hadron Collider. A 95% confidence level upper limit on the cross section times branching ratio of non--resonant production is set at 2.2 pb, while the expected limit is 1.0 pb. The corresponding limit observed for a narrow resonance ranges between 0.8 and 3.5 pb as a function of its mass.